A Distributed Leadership Perspective on Implementing Instructional Reform: A Case Study of an Urban Middle School. Issue 3 (May 2021) - Patterson, Jean A.; AlSabatin, Hala; Anderson, Amber; Klepacka, Martyna; Lawrence, John; Miner, Bradford
This qualitative case study examined the distribution of leadership and the implementation of an instructional reform in a low-performing urban middle school. Leadership for the instructional reform was widely distributed and stretched across formal and informal teacher leaders. School personnel were highly invested in the instructional model and implementation was high. The broad distribution of leadership across formal and informal leaders contributed to the school beginning to turnaround from lackluster academic performance and mediocre instruction to a culture where implementation of the instructional reform was expected, and where teacher collaboration and accountability were becoming the norm.